An exploratory study on enablers and barriers for onsite mechanisation in the Malaysian construction industry - Waris, M. (Construction Research Institute of Malaysia, 2015)
Onsite mechanisation in construction is characterized by the intensive deployment and usage of equipment. It requires different types of heavy equipment, vehicles and machineries for carrying out complex construction activities. The utilisation of heavy equipment increases construction productivity as well as reduces the dependency on intensive labour. Apart from this, the increasing trend of the Industrialised Building System (IBS) also needs greater mechanisation for erection and installation of large IBS components. This paper aims to investigate the current awareness of onsite mechanisation, the advantages in its adoption, and the barriers for the Malaysian construction industry. A questionnaire survey was conducted among a group of Construction Industry Development Board (CIDB) of Malaysia registered contractors. The important indings from the survey have indicated that there is a good understanding and application of mechanised practices among IBS contractors. It is further revealed that the need for onsite mechanisation has mainly come about to meet the timelines with a high speed of work and productivity. However, for medium and small size contractors, the implementation of onsite mechanisation is largely inhibited due to budget constraints as it is considered an extra inancial burden. The indings of this study will provide relevant authorities with informed understanding to develop potential policies and regulations to encourage mechanised practices for the Malaysian construction industry.